Wealth, consumption, and energy-efficiency investments - Anthony Britto; Joris Dehler-Holland; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2022)
We revisit optimal investment in energy-efficiency, presenting a decision framework built around the agent's wealth and wealth dynamic. An investment rule in the form of a trigger is derived such that the agent invests the first time the energy-carrier price crosses this threshold from below. Wealthier consumers, and those whose wealth grows faster, are seen to have less incentive to invest in energy-efficiency and alternative technologies. We investigate the market for heat pump upgrades in Germany and find scant evidence of an energy-efficiency gap. Modest carbon taxes coupled with subsidies suffice to generate stated policy goals in the short term.
Keywords: D15; D31; D81; H23; O33; Q48; Q49; 330; energy-efficiency gap; energetic building retrofits; wealth dynamics